Bidirectional Associations Between Mothers’ and Fathers’ Parenting Consistency and Child BMI - Westrupp, Elizabeth Mary; Giallo, Rebecca; Jansen, Pauline; Nicholson, Jan Maree; Wake, Melissa (My University, 2013)
BACKGROUND: Research suggests that general parenting dimensions and styles are associated with children’s BMI, but directionality in this relationship remains unknown. Moreover, there has been little attention to the influences of both mothers’ and fathers’ parenting. We aimed to examine reciprocal relationships between maternal and paternal parenting consistency and child BMI. METHODS: Participants were 4002 children and their parents in the population-based Longitudinal Study of Australian Children. Mothers and fathers self-reported parenting consistency, and children’s BMI was measured at 4 biennial waves starting at age 4 to 5 years in 2004. Bidirectionality between parenting and child BMI was examined by using regression analyses in cross-lagged models. RESULTS: The best-fitting models indicated a modest influence from parenting to child BMI, whereas no support was found for bidirectional influences. For mothers, higher levels of parenting consistency predicted lower BMI in children from Waves 1 to 2 and 3 to 4; for example, for every SD increase in mothers’ parenting consistency at Wave 1, child BMIz fell by 0.025 in Wave 2 (95% confidence interval: −0.05 to −0.003). For fathers, higher levels of parenting consistency were associated with lower child BMI from Waves 1 to 2 and 2 to 3. CONCLUSIONS: Parenting inconsistency of mothers and fathers prospectively predicted small increases in offspring BMI over 2-year periods across middle childhood. However, child BMI did not appear to influence parenting behavior. These findings support recent calls for expanding childhood overweight interventions to address the broad parenting context while involving both mothers and fathers.
Pediatrics
Keywords: Health -- Obesity; Families -- Parents and Parenting; Health -- Body size, BMI, Body image; Children; Families and relationships; Health and wellbeing; Children; Health; Families; Obesity; Body size, BMI, Body image; Parents and Parenting; Families and relationships; Health and wellbeing